2007
DOI: 10.1074/jbc.m701132200
|View full text |Cite
|
Sign up to set email alerts
|

NR4A Orphan Nuclear Receptors Modulate Insulin Action and the Glucose Transport System

Abstract: After observing that expression of two NR4A orphan nuclear receptors, NR4A3 and NR4A1, was altered by insulin in cDNA microarray analyses of human skeletal muscle, we studied whether these receptors could modulate insulin sensitivity. We found that both NR4A3 and NR4A1 were induced by insulin and by thiazolidinedione drugs (pioglitazone and troglitazone) in 3T3-L1 adipocytes. Furthermore, gene expression of NR4A3 and NR4A1 was reduced in skeletal muscles and adipose tissues from multiple rodent models of insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
109
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 29 publications
(17 reference statements)
13
109
0
2
Order By: Relevance
“…A representative figure (Figure 2) shows in graphical form a number of the orphan nuclear receptors that insulin resistant. There is little information available on the role of the NR4As in insulin resistance however, studies by Fu et al [24] found that Nur77 and Nor-1 were induced with 10 nM insulin in 3T3-L1 adipocytes cells at 1 h and 2 h, respectively. This is in collaboration to our studies were we show both Nur77 and Nor-1 induced by 10 nM insulin at 30 min and 2 h (Nur77) and 2 h (Nor-1).…”
Section: Resultsmentioning
confidence: 99%
“…A representative figure (Figure 2) shows in graphical form a number of the orphan nuclear receptors that insulin resistant. There is little information available on the role of the NR4As in insulin resistance however, studies by Fu et al [24] found that Nur77 and Nor-1 were induced with 10 nM insulin in 3T3-L1 adipocytes cells at 1 h and 2 h, respectively. This is in collaboration to our studies were we show both Nur77 and Nor-1 induced by 10 nM insulin at 30 min and 2 h (Nur77) and 2 h (Nor-1).…”
Section: Resultsmentioning
confidence: 99%
“…18 Both LXRa and LXRb increase target gene transcription by binding to DNA sequence motifs composed of two hexameric nucleotide direct repeats separated by four bases (DR-4). 19 Although in the earlier study, LXRa and NOR-1 were separately shown to participate in regulating genes involved in metabolic fuel usage, [7][8][9][10]16,20 our current studies in adipocytes identify a direct involvement of LXRa to regulate NOR-1 gene transcription through a DR-4 element in the NOR-1 promoter.…”
Section: Introductionmentioning
confidence: 89%
“…NR4A receptors were shown to contribute to the cAMP-dependent transcription of glucose-6-phosphatase in the liver, a key step in hepatic gluconeogenesis, 10 as well as to the regulation of genes involved in glucose and oxidative metabolism in skeletal muscle. 8,26 In adipose tissue, NR4As have been linked to the recruitment of GLUT4 receptors to the plasma membrane, resulting in improved insulin sensitivity, 7 and in brown adipocytes, NOR-1 contributes to the cAMP-dependent transcription of the Ucp1 gene, the induction of which is necessary for sustained adaptive thermogenesis. 9 Our finding of another transcriptional regulatory pathway to regulate NR4As, and the NOR-1 gene in particular in response to LXR, underscores the fact that we still do not know the full extent to which there is cross-talk between the nuclear receptor families to modulate each other's expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Ucp3 is involved in lipid metabolism (GO:6629). Cluster 2 includes five genes Hepattic protein EIIH, 15) Nr4a3, 16) Adrb3, [17][18][19][20] Adiponectin, 21) and Rbp4. 22,23) In particular, Nr4a3 and Adrb3 genes were involved in responses to stimulus (GO:50896), and Adiponectin genes were involved in lipid metabolism (GO:6629).…”
Section: Microarray Analysis Of Gene Expression Profiles In Diabetes-mentioning
confidence: 99%